Effect of Displacement Damage on Tantalum Oxide Resistive Memory. (13th June 2017) - Holt, Joshua S.; Beckmann, Karsten; Alamgir, Zahiruddin; Yang-Scharlotta, Jean; Cady, Nathaniel C.
ABSTRACT: The radiation environment of space poses a challenge for electronic systems, in particular flash memory, which contains multiple radiation-sensitive parts. Resistive memory (RRAM) devices have the potential to replace flash memory, functioning as an inherently radiation resistant memory device. Several studies indicate significant radiation resistance in RRAM devices to a broad range of radiation types and doses. In this study, we focus on the effect of displacement damage on tantalum oxide-based RRAM devices, as this form of damage is likely a worst-case scenario. An Ar + (170 keV) ion beam was used to minimize any contribution from ionization damage, maximizing the effect of displacement damage. Fluence levels were chosen to generate enough oxygen vacancies such that devices in the high resistance state (HRS) would likely switch to the low resistance state (LRS). More than half of devices tested at the highest fluence level (1.43E13 ions/cm 2 ) switched from HRS to LRS. The devices were then switched for 50 set/reset cycles, after which the radiation-induced resistance shift disappeared. These results suggest that device switching may mitigate radiation damage by accelerating oxygen vacancy-interstitial recombination.